Pengaruh latar belakang pendidikan dan pekerjaan orang tua terhadap kemampuan membimbing matematika anak (survey pada taman kanak-kanak di Kecamatan Koto Tangah) - Zahra, Diniati; Eliza, Delfi (Universitas Negeri Padang, 2021)
Early childhood education needs to develop mathematics. The process of mathematical development in children does not escape the guidance and role of parents. Factors supporting parental guidance include education and parental occupation. This study aims to describe the effect of parents' educational background and occupation on the ability to guide children's mathematics. This study uses a descriptive correlational quantitative method with 186 parents of kindergarten children in the Koto Tangah sub-district as respondents. Analysis of research data was carried out using the percentage of multiple regression with dummy variables using SPSS 26. Data collection from the study used a questionnaire validated by expert judgement techniques and reliability test using Cronbach's alpha formula with the results obtained that is 0.90. The research findings are (1) in terms of parental education, it is in a good category in encouraging children's development, (2) in terms of parents' work, it is in a good category in improving the ability of teachers to monitor children, (3) the effect on increasing mathematical abilities. ,5%, (4) the effect of work on the ability to encourage mathematics by 7.1%, (5) gender does not affect the ability to develop, (6) work and gender together on the ability to develop mathematics by 8 ,3%. (7) overall education, occupation and gender contribute or influence the ability to guide children's mathematics.